Differences in the Lateral Compartment Joint Space Width After Anterior Cruciate Ligament Reconstruction: Data From the MOON Onsite Cohort. Issue 4 (March 2018) - Jones, Morgan H.; Spindler, Kurt P.; Andrish, Jack T.; Cox, Charles L.; Dunn, Warren R.; Duryea, Jeff; Duong, Carol L.; Flanigan, David C.; Fleming, Braden C.; Huston, Laura J.; Kaeding, Christopher C.; et al.
Background: Anterior cruciate ligament (ACL) reconstruction can effectively return athletes to the playing field, but they are still at risk of developing posttraumatic osteoarthritis (PTOA). No studies have used multivariable analysis to evaluate the predictors of radiographic PTOA in the lateral compartment of the knee at short-term follow-up after ACL reconstruction. Purpose: To determine the predictors of radiographic joint space narrowing in the lateral compartment 2 to 3 years after ACL reconstruction in a young, active cohort. Study Design: Cohort study; Level of evidence, 2. Methods: A nested cohort of 358 patients from the Multicenter Orthopaedic Outcomes Network (MOON) prospective cohort who were aged ≤33 years, were injured playing a sport, and had never undergone surgery on the contralateral knee were followed up 2 years after ACL reconstruction with questionnaires and with weightbearing knee radiographs using the metatarsophalangeal (MTP) joint technique. The joint space width in the lateral compartment was measured using a semiautomatic computerized method, and multivariable predictive modeling was used to evaluate the relationship between meniscus treatment, cartilage injury, graft type, and joint space while adjusting for age, sex, body mass index, and Marx activity score. Results: The mean lateral joint space width was 0.11 mm narrower on the ACL-reconstructed knee compared with the contralateral healthy knee (7.69 mm vs 7.80 mm, respectively; P < .01). Statistically significant predictors of a narrower joint space width on the ACL-reconstructed knee included lateral meniscectomy ( P < .001) and a Marx activity score less than 16 points ( P < .001). Conclusion: This study identifies lateral meniscectomy and a lower baseline Marx activity score to be predictors of radiographic joint space narrowing in the lateral compartment 2 to 3 years after ACL reconstruction in young, active patients without a prior knee injury.